Pengaruh Kompetensi dan Kompensasi terhadap Kinerja Karyawan pada Hotel Aneka Lovina Villas and Spa Tahun 2019 - I Made Armada; Komang Krisna Heryanda (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effect of (1) competence and compensation for employee performance, (2) competence for compensation, (3) competence for employee performance, and (4) compensation for employee performance at various Lovina Villas And Spa hotels. The research design used in this study is causal quantitative. The subjects of this study were employees at the Hotel Aneka Lovina Villas and Spa and the object was competence, compensation, and employee performance. The population in this research is all employees of all employees who work at Aneka Hotel Lovina Villas and Spa, amounting to 44 employees. All populations are made as observation units, therefore this study is included as population research. Data collected by questionnaire technique, then analyzed by path analysis. The results showed that, (1) competence and compensation had a positive effect on employee performance, (2) competence had a positive effect on compensation, (3) competence had a positive effect on employee performance, and (4) compensation had a positive effect on employee performance at Aneka Lovina Hotel Villas and Spa. Keywords: employee performance, compensation, competence